Pendampingan Perizinan PIRT dan Sertifikasi Halal Produk Makanan Ringan Pada Pelaku UMKM di Desa Balesari, Windusari, Magelang - Dian Marlina Verawati; Rian Destiningsih; Ivo Novitaningtyas (Universitas Mathla'ul Anwar Banten, 2021)
COUNSELING TO FOOD AND BEVERAGES MSMEs ABOUT PIRT LICENSING AND HALAL CERTIFICATION IN BALESARI VILLAGE, WINDUSARI, MAGELANG. This PKM aims to increase the understanding of food and beverages MSMEs in Balesari Village, Windusari, Magelang, regarding the importance of PIRT licensing and halal certification to increase the selling value of products and also consumer buying interest. The implementation of this PKM is done by the method of lectures, tutorials, and discussions. The results of this PKM program are (1) MSMEs understand the importance of PIRT licensing and halal certification, and are motivated to proceed with it, (2) MSMEs understand PIRT licensing procedures, and (3) MSMEs understand procedures for halal certification. Thus, consumer buying interest and consumer trust are expected to increase through the existence of a PIRT number and a halal label. Moreover, it is also expected to increase the product sales and the welfare of the community in Balesari Village, Windusari, Magelang.